Critical slowing down theory provides early warning signals for sandstone failure - Tang, Yao; Zhu, Xing; He, Chunlei; Hu, Jiewei; Fan, Jie (Frontiers in Earth Science, 2022)
The critical point of rock mass transition from stable to unstable states is significant for the prevention and control of rock engineering hazards. This study explores the precursor characteristics of instability in sandstone containing prefabricated fractures and intact sandstone based on critical slowing down theory (CSD). The results demonstrate that as the input energy drives the dissipation energy dynamic system toward the critical point of two states, the input energy leads to the appearance of a CSD phenomenon, which is manifested by the increase in CSD metrics (skewness, kurtosis, coefficient of variation) and autoregressive model metrics (variance, autocorrelation coefficient). The CSD characteristics of different dissipation energy dynamical systems are different, resulting in different times of CSD phenomena for different systems. In addition, the angle of the sandstone fracture also affects the characteristics of the dissipation energy dynamical system and thus the appearance time of the precursor information. The precursor time of the sandstone containing 45° parallel fractures appears earliest among all rock samples, and the ratio of the appearance time of the precursor point to the failure time of all rock samples reaches more than 80%, which has good timeliness; the stress of the precursor point reaches more than 80% of the peak stress, which corresponds to the plastic stage in the loading process, indicating that the CSD indicators constitute an effective monitoring index, which can provide an important reference for the stability monitoring and early warning of the field rock project.